T Tingkat Kecemasan Remaja yang Menggunakan Smartphone di SMK Negeri 1 Martapura Kabupaten Banjar Tahun 2022 - Sitanggang, Yohana Agustina; Halimah, Nor (Journal of Nursing Invention, 2023)
Conclusion: Teenagers who use smartphones only experience mild anxiety. It is hoped that schools will provide education about the impact of using smartphones as an effort to prevent anxiety and the negative impacts of using smartphones.